2013
DOI: 10.1111/nph.12271
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem‐level controls on root‐rhizosphere respiration

Abstract: SummaryRecent advances in the partitioning of autotrophic from heterotrophic respiration processes in soils in conjunction with new high temporal resolution soil respiration data sets offer insights into biotic and environmental controls of respiration. Besides temperature, many emerging controlling factors have not yet been incorporated into ecosystem-scale models. We synthesize recent research that has partitioned soil respiration into its process components to evaluate effects of nitrogen, temperature and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(157 citation statements)
references
References 168 publications
(265 reference statements)
7
145
2
3
Order By: Relevance
“…For researchers primarily interested in an average growing season 14 C respiration value, this study corroborated previous work suggesting that seasonal variation in respired 14 CO 2 is substantial (Hicks Pries et al, 2013;Hirsch et al, 2003;Hopkins et al, 2013;Schuur and Trumbore, 2006). At a minimum, sampling time points at the beginning, middle, and end of the growing season are ideal to capture the seasonal progression of new C additions.…”
Section: Utility and Limitations Of 14 Co 2 For Understanding Soil Mesupporting
confidence: 70%
See 3 more Smart Citations
“…For researchers primarily interested in an average growing season 14 C respiration value, this study corroborated previous work suggesting that seasonal variation in respired 14 CO 2 is substantial (Hicks Pries et al, 2013;Hirsch et al, 2003;Hopkins et al, 2013;Schuur and Trumbore, 2006). At a minimum, sampling time points at the beginning, middle, and end of the growing season are ideal to capture the seasonal progression of new C additions.…”
Section: Utility and Limitations Of 14 Co 2 For Understanding Soil Mesupporting
confidence: 70%
“…Our results indicated that heterotrophic 14 C is dynamic and sensitive to immediate substrate availability, and that experimental manipulations to isolate heterotrophic and autotrophic activity can substantially impact estimates of heterotrophic 14 C. Inputs of new photosynthates over the growing season, which have been shown to decrease the 14 C content of root respiration (Hopkins et al, 2013), may also lead to decreases in the 14 C content of microbial respiration. Studies that make use of 14 CO 2 measurements for examining disturbance or climatic change impacts should be interpreted with an understanding that respired 14 CO 2 can fluctuate seasonally by 40 ‰, and that this variability may reflect not only changes in root contributions, but possibly root impacts on 14 C of heterotrophic respiration as well.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The potential biological mechanisms that would lead to diel variation in δ 13 C of respiration have been recently reviewed (Werner and Gessler, 2011) and include variation in respiratory substrate, isotopic fractionation, and/or changes in relative amounts of component fluxes such as autotrophic (rhizospheric) and heterotrophic respiration. There is compelling evidence for a short-term linkage between photosynthesis and belowground respiration (Kuzyakov and Gavrichkova, 2010), almost certainly mediated by the roots and their symbionts (Hopkins et al, 2013;Savage et al, 2013). Several studies have highlighted isotopic signals in respiration from the soil or whole forests that appear to be influenced by photosynthetic response to humidity or water availability (see reviews by Bowling et al, 2008;Brüggemann et al, 2011), which might be expected to lead to diel changes in δ 13 C of soil efflux.…”
Section: Discussionmentioning
confidence: 99%